2015
DOI: 10.4103/0366-6999.169106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Culture Supernatant Derived from Trichophyton Rubrum Grown in the Nail Medium on the Innate Immunity-related Molecules of HaCaT

Abstract: Background:Trichophyton rubrum is superficial fungi characteristically confined to dead keratinized tissues. These observations suggest that the soluble components released by the fungus could influence the host immune response in a cell in contact-free manner. Therefore, this research aimed to analyze whether the culture supernatant derived from T. rubrum grown in the nail medium could elicit the immune response of keratinocyte effectively.Methods:The culture supernatants of two strains (T1a, TXHB) were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…Our previous studies have already confirmed that TLR2 and TLR4 were involved in the immune response to T. rubrum infection. 8,9 In the present study, our results showed a suppressed native immune response in this patient with lower expression of TLR2 and no significant change of TLR4 at the protein level regardless of the presence of fungal infection or not, which might result in the susceptibility to T. rubrum infection in KID syndrome. Although the expression of TLR2 presented a small increase at the transcription level, it might be because some potential inhibitory/regulation factors in the KID syndrome patient influence the translation process of TLR2 protein.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…Our previous studies have already confirmed that TLR2 and TLR4 were involved in the immune response to T. rubrum infection. 8,9 In the present study, our results showed a suppressed native immune response in this patient with lower expression of TLR2 and no significant change of TLR4 at the protein level regardless of the presence of fungal infection or not, which might result in the susceptibility to T. rubrum infection in KID syndrome. Although the expression of TLR2 presented a small increase at the transcription level, it might be because some potential inhibitory/regulation factors in the KID syndrome patient influence the translation process of TLR2 protein.…”
Section: Discussionsupporting
confidence: 47%
“…Toll‐like receptors (TLR) are important pattern recognition receptors in mammals, and TLR2 and TLR4 play a crucial role in the host defense fungus infection . Our previous studies have already shown that keratinocyte can recognize T. rubrum , and induce native immune response through TLR2 and TLR4 . In the present study, we describe a rare Asian case of KID syndrome accompanied by disseminated cutaneous T. rubrum infection with mutation p.G12R of GJB2 .…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…A recent study showed that neither the IL-17 response nor adaptive immunity was required for fungal control of T. rubrum ( 35 ). Moreover, T. rubrum was reported to induce IL-1β production by macrophages, which, in turn, played essential roles in the immune response against T. rubrum ( 36 ), and the culture supernatant of T. rubrum was further shown to activate the innate immune response of HaCaT cells ( 37 ). The findings of these studies agree with our results showing that keratinocytes stimulated with EVs from T. interdigitale showed increased production of NO and proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%